Revisiting Jurisdiction of Individual Labour Disputes in the Republic of Kazakhstan: Comparative Legal Analysis of the Labour Law Application in Countries Near and Far Abroad - GALIAKBAROVA, Guzal Gazinurovna; ZHARKENOVA, Svetlana Bakhytovna; KULMAKHANOVA, Lyazzat Shalbaevna (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
Background/Objectives: This article deals with the specifics of jurisdiction of individual labor disputes in the Republic of Kazakhstan, sharing also experience of certain European countries (Switzerland, France, Italy, Sweden) and CIS-states (Ukraine, Belarus). The authors point out shortcomings of this issue that have been discovered in the latest Labor Code of the Republic of Kazakhstan. Ways of improving legal regulation of the procedure for resolving individual labor disputes in Kazakhstan are proposed based on foreign practice studies. The relevance of this matter is dictated by the fact that at the moment. Methods: Currently, legal regulation of individual labor disputes in Kazakhstan is a key matter of legal labor relations. Such scientific methods as scientific research, comparative analysis and generalization were used in the course of this research. Foreign and domestic sources were used for this research, and a list of such resources can be found in the References section. Findings: According to the analysis of the Kazakh and Russian procedural legislation, there is a steady trend towards expanding ways of resolving legal disputes in court in general, labor disputes in particular, including those between economic operators (an employee and the employer), which appears to correspond to the current development of economic relations. Hence, there is an increasing role of specialized labor courts, which may play an important role in Kazakhstan as well in matters of correct and exhaustive resolution of labor disputes on the whole, and individual disputes in particular, provided the experience of certain EC states is used and introduced correctly. Application/Improvements: The authors conclude that it is necessary to study an institute of individual labor disputes at the current stage of the society and state development, as long as such institution regulates one of the most important and integral part of legal procedural labor relations. Therewith, reasonable application and awareness of standards of such institution shall prevent any abuse on the part of the employer and an employee. The authors justified their conclusion on the applicability of experience of certain European countries with labor courts and labor justices functioning there to introduce the experience of certain foreign countries in the use of a simplified procedure of resolution of labor disputes, aiming at accelerated resolution of such disputes and reducing the load on such courts significantly.